Adolescência, ato e medida: o que a jovem tem a dizer - Paula Saraiva Rocha (2016)
This study aims to investigate the adolescent's perspective about their misdemeanors and fulfillment of socio internment measure. Therefore, we analyzed the effect of the deprivation of liberty may cause in the lives of teenagers, from reports collected a socio-educational unit in Belo Horizonte. We discussed this work, the concept of adolescence and how it manifests itself in contemporary, using psychoanalysis as a theoretical referential. Puberty awakening causes restlessness and the solution found by adolescents often gives the act road. The act may be an attempt to tell the impossible to be said before this moment of transition from childhood to adulthood. If this act is infracional, it produces consequences that lead the teen to enter the childcare system. Was held a brief historical background on previous legislation until the arrival of the Children and Adolescents and the National Socio-Educational System. It is argued that in this context, where it is proposed to comply with standards, rules, activities and routines, there must be a space in which institutional imperatives can be subverted, causing the teenager to reveal as subjects of law and desire.